Research of influence the parameters of a dispersive environment on stability of the colloidal silver stabilized by quarternary ammonium compounds - Andrei Vladimirovich Blinov; Alexander Vladimirovich Serov; Anastasia Alexandrovna Blinova; Arina Sergeevna Nadeina; Alexander Aleksandrovich Kravtsov (Наука. Инновации. Технологии)
Research of stability of diverse colloidal systems is main and applied interest. Silver in a nanodimensional state possesses bactericidal properties and can be applied in the industry as the disinfecting agent [6]. Results of research of various factors on stability of the preparation of the colloidal silver are presented in the work. The most important factors which have a influence on stability of colloidal system are: hold time, temperature of solution, ionic force of solution and active acidity. These factors allow to determine conditions where the preparation on a basis of colloidal silver can successfully be applied and not aggregate. The experiment planning matrix has been made for research of influence of each factor. Experimental date were processed by using of neural networks [1, 2]. Were got the response surface which describe adequately the influence the parameters of a dispersive environment on stability of the preparation of the colloidal silver.